Food waste and its associated environmental impacts in workplace buffet-style canteens in Beijing, China - Zhang, Dan; Zhang, Panpan; Xue, Li; Wu, Liang (Frontiers in Sustainable Food Systems, 2024)
Introduction Food waste is a significant global challenge, with critical implications for food security, ecosystem services, biodiversity, and human health. Despite growing attention to food waste in food service sectors, workplace buffet-style canteens—particularly in China—remain understudied. This research addresses this gap by quantifying food waste and evaluating its environmental impacts in workplace buffet-style canteens in Beijing, China. Methods Field surveys were conducted in four workplace buffet-style canteens in Beijing during August and September 2021. Systematic sampling yielded 656 valid samples. Food waste was measured using a direct weighing method, categorized into eight food types, and analyzed for its environmental impacts using carbon, nitrogen, phosphorus, water, and ecological footprint metrics. Conversion factors were applied to translate cooked food into raw agricultural equivalents for consistent impact assessment. Results The study found an average daily per capita food waste of 158.4 g, with lunch contributing the highest waste (78.8 g) compared to breakfast and dinner. While vegetables were the largest contributors by weight, livestock products, though comprising only 29.9% of waste, accounted for the majority of environmental impacts, including 96.7% of the ecological footprint and 85.7% of the water footprint. Self-run canteens generated less waste across all meals compared to outsourced ones, and higher food and cuisine diversity were associated with increased food waste. Discussion The findings underscore the influence of dietary habits, management models, and food diversity on food waste generation. Livestock product waste poses disproportionate environmental burdens, highlighting the need for targeted interventions such as portion control and educational campaigns on sustainable dining practices. These results provide valuable insights for policymakers aiming to align food waste reduction strategies with Sustainable Development Goal 12.3.